Smart and Healthy Generation: Sexuality Education and Health Check-Up with Garuda Parang Catholic Junior High School Students in Magetan - Kolektus Oky Ristanto; Cicilia Deandra Maya Putri; Audrey Gabriella Titaley; Maria Mediatrix Andita Garindra Putri (Jurnal Pengabdian Masyarakat Mentari, 2026)
The community service program "Smart and Healthy Generation: Sexuality Education and Health Check-Up with Garuda Parang Catholic Junior High School Students in Magetan" was implemented to address the need for improved reproductive health literacy and healthy lifestyle behaviors among early adolescents. Adolescents at the junior high school level are in the pubertal phase, characterized by significant physical, emotional, and social changes, and thus require a comprehensive understanding of sexuality, reproductive health, and the prevention of risk behaviors. However, research shows that the level of sexual literacy among Indonesian adolescents is still low, while access to inaccurate information from digital media is increasing. Therefore, appropriate and adolescent-friendly educational interventions are urgently needed to support the development of healthy and responsible behaviors. This activity aims to: (1) increase students' understanding of healthy sexuality, puberty, boundaries, and sexual violence prevention; and (2) conduct basic health checks, including nutritional status, blood pressure, and personal hygiene. The activities include interactive lectures, group discussions, and health checks by medical personnel and educators. The program results showed an average 32% increase in students' knowledge based on pre-tests and post-tests, an increase in positive attitudes toward healthy behaviors, and initial findings of actionable health conditions such as mild anemia and unhealthy body mass index. These findings are consistent with previous studies confirming that participatory health education is effective in improving adolescent health literacy.